The Research on the Valuation of Chinese Internet Companies------Based On DCF-BS Method - SHI, BOHAN (2017)
The concept of "Internet plus" was first mentioned in NPC &CPPCC (National People Congress and Chinese People Political Consultative Conference) in 2015. With the advent of Internet Plus era, the development of Internet industry has been accelerating. At the same time, the issue of how to accurately assess the value of Internet enterprises is widely valued.